-4(w+5)=-2w-26

Simple and best practice solution for -4(w+5)=-2w-26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(w+5)=-2w-26 equation:


Simplifying
-4(w + 5) = -2w + -26

Reorder the terms:
-4(5 + w) = -2w + -26
(5 * -4 + w * -4) = -2w + -26
(-20 + -4w) = -2w + -26

Reorder the terms:
-20 + -4w = -26 + -2w

Solving
-20 + -4w = -26 + -2w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2w' to each side of the equation.
-20 + -4w + 2w = -26 + -2w + 2w

Combine like terms: -4w + 2w = -2w
-20 + -2w = -26 + -2w + 2w

Combine like terms: -2w + 2w = 0
-20 + -2w = -26 + 0
-20 + -2w = -26

Add '20' to each side of the equation.
-20 + 20 + -2w = -26 + 20

Combine like terms: -20 + 20 = 0
0 + -2w = -26 + 20
-2w = -26 + 20

Combine like terms: -26 + 20 = -6
-2w = -6

Divide each side by '-2'.
w = 3

Simplifying
w = 3

See similar equations:

| 3x^7-3x^2=0 | | 3(10n-5)= | | 3(4+6x)=48 | | a+5-2a= | | -4(5x-10)=40 | | 9a+2b=766.97 | | 4x+5=8x-31 | | 3y-y=-5+30 | | 17-2x=x+8 | | 34=3(w-2)-7w | | 6(3x+6)=-180 | | -0.2+x=1.4 | | 16x^4-a^4=0 | | 17-2x+x=8 | | 23g+1=19 | | 5+-10*2= | | (16x-2)=(8x+14) | | T(n)=3n+1 | | -3(5p+2)-2(3-17p)=3(6+6p) | | 3+5x=-3x-93 | | 20x+7y=3fory | | 8m-24=4 | | 6x+5=-3x+104 | | -5x+4=68+3x | | -2x+10+7x=65 | | 4+7x+x=68 | | 180=(30+x)+30+9x | | 8.5+x=7.1-x | | 62=y-19 | | x^4-8x^3+24x^2-32x=65 | | 15y-9y= | | -3-y=6 |

Equations solver categories